Technological Unemployment and an Attainable Way Out - Pavlova, Adelina; Špecián, Petr; Prokop, Jaromír; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2015)
The purpose of the thesis is to analyze the available information on the technological unemployment issue. The hypothesis of the thesis is that displacement of workers because of technological development has reasonable chances to happen in the future. Technological unemployment is hotly debated issue. Some part of economists argue that technological unemployment is a short-term problem; others see it as a risk for society. Thus, at this stage it is important to identify controversy in studies, analyze proposed policies and suggest the possible strategies. In order to gain the in depth knowledge required for the thesis a literature synthesis methodology was used. The concluding recommendations for researchers and policy makers include three important point to design an appropriate policy measure: number of population in a region, specialization of a region, previous placement of a worker. The effective solution is considered a mix of policies to target the problem from different prospective.
Vedoucí práce: Petr Špecián
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses